Respons pemikir Islam terhadap modeniti : wacana sains Islam sebagai kajian kes di Malaysia / Maisarah Hasbullah - Maisarah, Hasbullah (2012)
In assessing the significance and position of science in modern society in Malaysia which has a majority Muslim population, this study intends to see the relationship between Islam, science and modernity. The response towards modernity is viewed in two dimensions, the social dimension that involves organization such as Akademi Sains Islam Malaysia (ASASI), and the dimension of thought based on selected Muslim thinkers. This thesis describes how Muslim thinkers response to the challenged posed by modernity through the discourse of Islamic science and by using the arguments of history and philosophy. The response of Muslim thinkers on modernity lead to the epistemological dimension to understand, review, and analyze their thinking in order to understand the complex relationship between Islam, science and modernity. In the Malaysian context, the relationship between science, Islam and modernity in Islamic science discourse involves changing attitude towards the more critical adoption for modernity, then it expanded to a critique of science. Similarities and differences exist between the critique of science by the Muslim thinkers and Western thinkers, which includes criticizing or rejecting the image of modern science, but not completely rejecting modernity.